Digital subtraction analysis after application of silver diamine fluoride on early proximal caries lesions: a 12-month randomized controlled trial - Rinrada Pirompak; Chutima Trairatvorakul; Suchaya Pornprasertsuk-Damrongsri; Thipawan Tharapiwattananon; Pornkawee Charoenlarp; Ratichanok Nantanee (Scientific Reports)
Abstract The aim of the study was to examine the mean mineral density (MD) change in early proximal enamel caries lesions after applying silver diamine fluoride (SDF) using digital subtraction radiographic analysis at 6 and 12 months. A split-mouth, triple-blind, randomized controlled trial was conducted with thirty healthy participants aged 13–30 years old. Two active non-cavitated proximal caries lesions in different quadrants of each participant were randomly sampled and allocated to a test (38% SDF) and a control group (deionized water). Digital radiographs at baseline, 6 and 12 months were taken, and digital subtraction radiographic analysis was performed. The SDF group demonstrated a significantly higher mean MD on subtraction radiographs compared with the control group, after adjusting for baseline lesion depth and time, and for clustering within participants over time. The adjusted mean difference was 1.0 [95% CI 0.2, 1.9]. Therefore, applying SDF at baseline and 6 months resulted in significant remineralization compared with the control group over the 12-month period. These findings suggested that applying SDF can serve as an effective alternative treatment option for remineralizing early caries lesions on proximal surfaces.